Clinical signs of caprine arthritis-encephalitis and disease-related pathomorphological changes - V. Yu. Koptev; N. А. Shkil; N. Yu. Balybina; I. N. Penkova (Ветеринария сегодня)
Over the past ten years, the small ruminant population in the Russian Federation grew sharply, especially goat population in backyards and on small-scale farms. Alongside with the population growth, clinical signs of some sporadic diseases or diseases that had not been previously registered were detected in animals. Caprine arthritis-encephalitis (CAE) is one of such diseases. It is a chronic infectious disease caused by a small ruminant lentivirus (SRLV) of the Retroviridae family, which includes four genotypes, of which genotypes A (maedi-visna – MVV virus) and B (caprine arthritis-encephalitis virus – CAEV) are of epizootic significance. The disease is characterized by long asymptomatic viral transmission and is associated with progressive lesions in the respiratory organs, joints and udder. The disease also affects nervous system in kid goats aged between 2 and 3 months. Clinical signs of caprine arthritis-encephalitis are not pathognomonic; therefore, it is often misdiagnosed, thus, resulting in a barrier to effective treatment. Given the fact, the issue of antemortem and postmortem diagnosis of caprine arthritis-encephalitis is still urgent, because most veterinary specialists have never encountered this disease and the data available in the literature often do not fully cover all clinical details and pathomorphological features. Therefore, the purpose of the work is to study CAE clinical signs and pathomorphological changes. The article describes in detail clinical manifestation of this disease, postmortem lesions in organs and tissues of the sick animals. The results obtained suggest that the destructive changes in the exposed organs are irreversible and, consequently, there is no effective treatment.